Awake airway management for retrograde injection laryngoplasty in a high-risk oncologic patient with severe trismus: a case report - Murugesan, Anand; Tanjore, Srikanth; Mohan, Prethiv Raj; Ramalingam, Shrinidhi; Vidhyadharan, Sivakumar; Duarah, Sandip; Perumal, Janakan Sennava; Hedne, Naveen (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Advanced head and neck malignancies often present with complex airway and systemic challenges that critically influence anesthetic management. We report a high-risk patient with carcinoma of the tonsil and widespread metastases who had a prior history of pseudoaneurysm rupture of facial artery treated with embolization, complicated by intra-procedural cardiac arrest, atrial fibrillation, and subsequent dialysis-dependent acute renal failure. The patient later presented with unilateral vocal cord palsy requiring injection laryngoplasty. Severe trismus, compromised pulmonary reserve due to metastatic disease, and underlying cardiac dysfunction rendered general anesthesia particularly hazardous. An awake airway approach using 4% lignocaine nebulization, trans-tracheal block, and dexmeditomidine sedation was employed to maintain spontaneous ventilation while providing optimal procedural conditions. This enabled successful completion of the shared airway procedure using a retrograde technique without complications. This case highlights the importance of individualized anesthetic strategies in high-risk oncologic patients and underscores the value of regional airway anesthesia combined with conscious sedation as a safe alternative to general anesthesia.